Kajian Literatur Perbandingan Teknologi EPON dan GPON pada Jaringan Akses Fiber Optik - Muhammad Rizky Irawan; Andi Ahmad Dahlan; Lifwarda Lifwarda; Yulindon Yulindon (Kampus Akademik Publiser, 2026)
The increasing demand for high-speed broadband services has driven the adoption of Fiber To The Home (FTTH) technology based on Passive Optical Network (PON). The two primary technologies dominating current implementations are Ethernet Passive Optical Network (EPON) and Gigabit Passive Optical Network (GPON). This study aims to conduct a systematic literature review providing an in-depth comparison between EPON and GPON regarding technical specifications, Quality of Service (QoS) performance, and economic implications. The methodology employed is a Systematic Literature Review (SLR), evaluating scientific publications from 2020 to 2025. The results indicate that GPON offers significant advantages in downstream capacity (2.488 Gbps), protocol efficiency reaching 92%, and granular bandwidth management through the T-CONT mechanism, making it ideal for large-scale triple-play services. Conversely, EPON provides a simpler architecture, 20-30% lower capital expenditure (CAPEX), and symmetric speeds (1.25 Gbps) suitable for business or rural traffic needs. This research concludes that technology selection must be based on subscriber density and operational budget, where GPON excels in dense metropolitan areas, while EPON remains competitive for cost-sensitive market segments.